1999
DOI: 10.1046/j.1365-2265.1999.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human growth hormone in elderly osteoporotic women

Abstract: These results indicate that GH attenuates the decrease in muscle strength and bone mass as well as the gain of abdominal fat with ageing in elderly women. The present data provide useful information about the application of GH treatment in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 64 publications
(82 reference statements)
3
26
1
1
Order By: Relevance
“…Furthermore, GH treatment in GH-deficient adults increased BMD at the lumbar spine and femoral neck for up to 30 -36 months, with a plateau thereafter (28). Our previous study (14) revealed that, when BMD continued to be monitored after discontinuation of GH treatment for another 48 weeks, significant increases in radial and lumbar BMD (8:1^2:1% and 3:8^1:4% above pretreatment values respectively) were observed in elderly women with osteoporosis. In the previous study, GH was administered at 0.00595 mg/kg per day for the first 4 weeks and subsequently at 0.0119 mg/kg per day for 48 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, GH treatment in GH-deficient adults increased BMD at the lumbar spine and femoral neck for up to 30 -36 months, with a plateau thereafter (28). Our previous study (14) revealed that, when BMD continued to be monitored after discontinuation of GH treatment for another 48 weeks, significant increases in radial and lumbar BMD (8:1^2:1% and 3:8^1:4% above pretreatment values respectively) were observed in elderly women with osteoporosis. In the previous study, GH was administered at 0.00595 mg/kg per day for the first 4 weeks and subsequently at 0.0119 mg/kg per day for 48 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…To establish the clinical utility of GH in osteoporosis in the elderly, GH treatment must be shown to have significant long-term anabolic effects without deleterious side effects. Some patients receiving GH treatment exhibited minor side effects such as edema and joint pain (14). We therefore used GH 0.00595 mg/kg per day for 48 weeks in the present study, which was half the GH dose used in our previous study (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth hormone has been used as a bone anabolic agent in GH-deficient patients [9,[20][21][22][23] and in some situations where the main factor causing osteoporosis was the decrease in osteoblastic function, such as anorexia nervosa [24], age [25] and idiopathic osteoporosis [26,27].…”
Section: Resultsmentioning
confidence: 99%